Up-regulation of Gr1 + CD11b + cell population in the spleen of NaClO-administered mice works to repair skin wounds - Mayu Hara; Naomi Nishio; Sachiko Ito; Masashi Akiyama (BioDiscovery, 2012)
In wound healing, early infiltration of neutrophils followed by macrophage infiltration are important defense mechanisms for repair of tissue damage. Here we examined the effects of neutrophils on wound healing. Administration of sodium hypochlorite (NaClO) to mouse skin induces neutrophil recruitment to the wound site and repeated administration of NaClO was shown to prolong wound healing. Examination of the spleens of mice whose wounds were repeatedly treated with NaClO, showed that GR-1+CD11b+ cells were up regulated in the recovery phase of wounding. Many of the GR-1+CD11b + cells in the mouse bone marrow were neutrophils, as indicated by a ring-shaped nucleus, and some of the cells were immature myeloid-lineage cells. GR-1+CD11b+ cells from bone marrow were sorted and injected intravenously to syngeneic Imprinting Control Region (ICR) mice. The mice that received GR-1+CD11b+ cells recovered faster than the mice injected with the control, phosphate buffer saline (PBS).